Latent profiles analysis of spiritual orientation and psychological well-being among female healthcare workers - Dikmen, Mualla; Elmali, Filiz (Springernature, 2026)
This study aimed to identify latent profiles of spiritual orientation (SO) and psychological well-being (PWB) among female healthcare workers and to examine how demographic factors predict profile membership. A total of 104 female healthcare professionals from two hospitals in eastern T & uuml;rkiye were recruited using purposive criterion sampling. Participants completed validated self-report measures assessing SO and PWB. Latent Profile Analysis (LPA) with varying means, equal variances, and covariances fixed to zero (Model 1) was conducted to uncover distinct profiles based on standardized mean scores. Four profiles were identified: Low Spirituality-Low Well-Being (5.8%), Moderate Spirituality-Low Well-Being (13.5%), High Spirituality-High Well-Being (61.5%), and Low Spirituality-High Well-Being (19.2%). The four-class solution demonstrated superior fit indices (BIC = 1737.0, entropy = 0.956) compared to alternative models. Multinomial logistic regression analysis revealed that education level, tenure, and marital status standing significantly predicted membership in the more adaptive profiles, particularly the High Spirituality-High Well-Being group. Notably, a moderate positive correlation (r = .40, p < .001) was observed between SO and PWB. These findings highlight the heterogeneity of spiritual-psychological functioning in female healthcare workers and underscore the potential buffering role of socioeconomic and professional factors. The person-centered approach employed in this study provides nuanced insight into the complex interplay between spirituality and well-being in high-stress healthcare environments. The results offer implications for designing individualized interventions that consider both the spiritual and emotional needs of healthcare workers.
Keywords: Spiritual orientation; Psychological well-being; Latent profile analysis; Female healthcare workers